1998
DOI: 10.1089/thy.1998.8.235
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Concentration of Interleukin-5 in Patients with Graves' Disease and Hashimoto's Thyroiditis

Abstract: We investigated serum levels of interleukin-5 (IL-5) in order to examine the role of T-helper 2 (Th2)-type immune response in the pathogenesis of autoimmune thyroid diseases. Serum levels of IL-5 were determined by a highly sensitive sandwich enzyme-linked immunosorbent assay in 42 patients with Graves' disease, 32 patients with Hashimoto's thyroiditis, 12 patients with silent thyroiditis, and 21 normal controls. Compared with serum levels in normal subjects (5.8 +/- 4.2 pg/mL), IL-5 was increased in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 15 publications
2
23
2
Order By: Relevance
“…On the other hand, a recent study shows that adipose tissue secretion of interleukin-6 is elevated in Graves' disease (36) even after restoration of euthyroidism. Some authors have found elevated cytokine concentrations in autoimmune hypothyroidism (37,38), as opposed to our finding of decreased MBL levels. In parallel to our findings, it has been shown that serum sIL-2R levels are positively modulated by thyroid hormone, mostly independently of thyroid autoimmunity (39 -41).…”
Section: P-valuescontrasting
confidence: 99%
“…On the other hand, a recent study shows that adipose tissue secretion of interleukin-6 is elevated in Graves' disease (36) even after restoration of euthyroidism. Some authors have found elevated cytokine concentrations in autoimmune hypothyroidism (37,38), as opposed to our finding of decreased MBL levels. In parallel to our findings, it has been shown that serum sIL-2R levels are positively modulated by thyroid hormone, mostly independently of thyroid autoimmunity (39 -41).…”
Section: P-valuescontrasting
confidence: 99%
“…Wahrenberg et al (24) have reported that adipose tissues from these individuals release several-fold higher levels of IL-6 than do similar tissues from control subjects. Circulating IL-6 levels have also been found to be elevated in Graves' disease (17)(18)(19)(20)(21)(22). Moreover, treatment of thyrotoxicosis fails to normalize these levels, suggesting strongly that they are a consequence of the underlying autoimmune process.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, IL-6 has generated considerable interest because it has been implicated in human autoimmune diseases and multiple myeloma (15,16). IL-6 and soluble IL-6R, like several other important cytokines, have been found to be elevated in patients with Graves' disease (17)(18)(19) and those with TAO (20 -23). IL-6 protein can be detected in s.c. fat in these patients (24).…”
Section: Il-1␤ Induces Il-6 Expression In Human Orbital Fibroblastsmentioning
confidence: 99%
“…10 All assays were done in duplicate. The detection limit of the assay was 4 pg/ml and the intra-assay and inter-assay coefficients of variation were 7% and 12%, respectively.…”
Section: Cytokine Assaymentioning
confidence: 99%
“…3,8 Consequently, differences in the pattern of cytokine secretion, especially that of IL-5 and IL-12, were further studied to identify a possible role of these cytokines in the pathogenesis of AITD. [9][10][11] Thyroid autoimmunity is being increasingly identified as the underlying cause of goitre in India subsequent to the implementation of the salt iodization program in the country. 12 Meanwhile, there is a paucity of literature on the immunopathogenesis of AITD among the Indian population.…”
mentioning
confidence: 99%